Establishment of a sequence-based typing system for BoLA-DRB3 exon 2 - Law, A.S.; Russell, George C.; Miltiadou, Despoina (My University, 2003)
A rapid, high-resolution sequence-based typing (SBT) system for BoLA-DRB3 exon 2 was developed. Amplification of the entire exon was achieved by a fully nested PCR with locus-specific primers and sequencing was performed directly on the PCR product. Heterozygous sequence data were obtained by automated sequence analysis of both alleles. Forward and reverse sequence data were assembled to improve identification of all heterozygous positions. Specific software (Haplofinder, Roslin Institute Software, Roslin, UK) was designed for allele assignment. Fifty-four females from a Holstein-Charolais resource herd cross, their 12 sires and five unrelated Holstein animals were used to establish the method. In parallel, these animals were typed by DRB3 polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) to confirm the results. Polymerase chain reaction-RFLP analysis defined 15 known types in the 71 animals, while SBT of the same animals showed 19 known alleles. Subsequently, 72 more animals from the same resource herd were typed by the established SBT method without PCR-RFLP typing. This SBT strategy and the Haplofinder software can be applied to the analysis of any polymorphic locus for which suitable locus-specific primers and allelic sequences are available.
Keywords: BoLA; Cattle; Class II; Major histocompatibility complex; Polymorphism; Sequence-based typing